The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jmd2.12163
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrotendinous xanthomatosis‐associated diarrhea and response to chenodeoxycholic acid treatment

Abstract: Background In patients with cerebrotendinous xanthomatosis (CTX), chronic diarrhea is one of the earliest and main symptoms of the disease. In the current study, we evaluated the characteristics of the diarrhea and its response to chenodeoxycholic acid (CDCA) therapy in a cohort of Dutch CTX patients. Methods We performed a retrospective review of medical records for 33 genetically confirmed CTX patients, and abstracted the characteristics of the diarrhea and the response to CDCA therapy (15 mg/kg/day up to 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Early recognition of CTX as a syndrome is important because supplementation with chenodeoxycholic acid may alleviate, and in some cases resolve GI symptoms and stabilize neurologic symptoms. 79,80,81…”
Section: Cerebrotendinous Xanthomatosismentioning
confidence: 99%
“…Early recognition of CTX as a syndrome is important because supplementation with chenodeoxycholic acid may alleviate, and in some cases resolve GI symptoms and stabilize neurologic symptoms. 79,80,81…”
Section: Cerebrotendinous Xanthomatosismentioning
confidence: 99%
“…24 Moreover, it can be the only clinical manifestation for many years. 202 While some studies describe the incidence of chronic diarrhea in 76% of cases, other reviews report a 20% (5/25). 32,202 However after checking the ethnicity of the cohort, one can see that 12/25 of patients were Asian.…”
Section: Diarrheamentioning
confidence: 99%
“…202 While some studies describe the incidence of chronic diarrhea in 76% of cases, other reviews report a 20% (5/25). 32,202 However after checking the ethnicity of the cohort, one can see that 12/25 of patients were Asian. That is important in light of reports comparing the incidence of chronic diarrhea in Chinese and Caucasian populations with results of 3.8% and 92%, respectably.…”
Section: Diarrheamentioning
confidence: 99%
See 1 more Smart Citation
“…It has a molecular formula of C 23 (OH) 2 H 37 CONHCH 2 CH 2 SO 3 H as an acidic compound combined with taurine and chenodeoxycholic acid. Previous studies of chenodeoxycholic acid have demonstrated that TCDCA is anti‐inflammatory, antipyretic, analgesic, and bacteriostatic and can regulate immune cells (Brass et al., 2020; Fan et al., 2019; Fiorucci & Distrutti, 2019; Nakhi et al., 2019). TCDCA also can promote apoptosis of mouse peritoneal macrophages (Fukumoto et al., 2002; Zan et al., 2020).…”
Section: What Is Known and Objectivementioning
confidence: 99%